Reading fluency: normative data for Romanian speaking population - Bodea Hategan, Carolina; Talas, Dorina; Costea-Bărluțiu, Carmen; Trifu, Raluca (Social Welfare: Interdisciplinary Approach, 2017)
The purpose of this study was to establish reading fluency norms for first grade students at the end of the school year in Romanian language using PEAFC (Proba de evaluare şi antrenare a fluenţei în citire/ The Assessment and Training of Reading Fluency Instrument, Bodea Haţegan & Talaş, 2014). A representative sample of 1977 first grade students (with ages between 7 and 8 years old) was assessed, girls (Ng=954) and boys (Nb=1023), from different counties from Romania (Nc=11), attending rural (Nr= 385) and urban (Nu=1592) elementary schools. Oral reading fluency norms were established on the linguistic structure of the words (monosyllabic, disyllabic, three syllable words and text words). The results of this study offer a new perspective on the reading fluency levels at the end of the first grade and will help the teachers and the specialists to identify students at risk for dyslexia and to start effective early intervention programs to improve reading fluency.
Keywords: reading fluency; oral reading fluency norms; reading abilities; dyslexia; poor reading; fluent readers